2020
DOI: 10.3390/catal11010008
|View full text |Cite
|
Sign up to set email alerts
|

Bis-NHC–Ag/Pd(OAc)2 Catalytic System Catalyzed Transfer Hydrogenation Reaction

Abstract: The bis-NHC–Ag/Pd(OAc)2 catalytic system (NHC = N-heterocyclic carbene), a combination of bis-NHC–Ag complex and Pd(OAc)2, was found to be a smart catalyst in the Pd-catalyzed transfer hydrogenation of various functionalized arenes and internal/terminal alkynes. The catalytic system demonstrated high efficiency for the reduction of a wide range of various functional groups such as carbonyls, alkynes, olefins, and nitro groups in good to excellent yields and high chemoselectivity for the reduction of functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In the recent 2 decades, the research of N-heterocyclic carbene (NHC) has been widely concerned because of its strong coordination ability. , A lot of metal complexes with peculiar structures using NHC as ligands have been reported. A part of these complexes possessed favorable application value in some fields, such as medicine and catalytic science. Besides, the NHC macrometallocycles as hosts have been used in host–guest chemistry. Compared to other types of hosts, cyclic NHC metal complexes contain multi-binding sites for guests, such as nitrogen atoms, π systems, and metal ions. The advantages of these NHC metal complexes are that they were easily prepared and had good stability to air or moisture. Cu 2+ as a heavy metal ion takes part in many life processes of human, animals, and plants. For example, excess or deficient copper in the body will lead to illnesses, such as Wilson’s and Alzheimer’s diseases. Besides, excess Cu 2+ can also destroy the environmental system and even affect the physiological processes in plants .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent 2 decades, the research of N-heterocyclic carbene (NHC) has been widely concerned because of its strong coordination ability. , A lot of metal complexes with peculiar structures using NHC as ligands have been reported. A part of these complexes possessed favorable application value in some fields, such as medicine and catalytic science. Besides, the NHC macrometallocycles as hosts have been used in host–guest chemistry. Compared to other types of hosts, cyclic NHC metal complexes contain multi-binding sites for guests, such as nitrogen atoms, π systems, and metal ions. The advantages of these NHC metal complexes are that they were easily prepared and had good stability to air or moisture. Cu 2+ as a heavy metal ion takes part in many life processes of human, animals, and plants. For example, excess or deficient copper in the body will lead to illnesses, such as Wilson’s and Alzheimer’s diseases. Besides, excess Cu 2+ can also destroy the environmental system and even affect the physiological processes in plants .…”
Section: Introductionmentioning
confidence: 99%
“…A study of different catalytic systems conducted by Feng et al [26] showed that by-products were formed on those systems that had strong acidic sites, namely Pd/SiO 2 , Pd/Al 2 O 3 , and Pd/TiO 2 , whereas high selectivity of Pd/C and Pd/NaY was observed, which was attributed to the lack of numerous strong acid sites. In the case of the hydrogenation of α,β-unsaturated carbonyl compounds the chemoselectivity of the hydrogenation to the unsaturated alcohol is of great importance, which has resulted in multiple studies being conducted on this topic [27][28][29][30][31]. To date, no reports of catalytic properties of amorphous magnesia in transfer hydrogenation have been published.…”
Section: Introductionmentioning
confidence: 99%